(untitled) (Productivity, 2020)
In the era of globalization. The competition of business became very sharp, either the domestic market or international market. In banking, world strategy is necessitated to face business competence that tight increasingly. There are challenges to achieving firm success. One thing that must be attended to get the aim of the firm is service quality. This research aims to find out kinds of service quality. That is, (Reliability), (responsiveness), (assurance), (empathy), (tangible) the influence ofÂ PT. Bank Tabungan Negara customer satisfaction (persero) Tbk, cabang Manado office. This research is using quantitative research. By using data analysis techniques validity test, reliability test, classic assumption test, linear doubled regression analysis, correlation coefficient, determination coefficient R2, and hypotheses test. Based on the result of partial the test, showed that (Reliability), (responsiveness), (assurance), (empathy), (tangible), the influence ofÂ PT. Bank Tabungan Negara customer satisfaction (persero) Tbk, cabang Manado office. Silmutan test showed that the Service Quality the simultan to the customer satisfaction PT. Bank Tabungan Negara (persero) cabang Manado office.